Pengaruh Likuiditas, Pertumbuhan Penjualan Dan Ukuran Perusahaan Terhadap Profitabilitas - Metyria Imelda Hutabarat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Food and beverage companies are industries that compete in the world market and make major contribution to the value of national exports. Companies that have good profitability have a good reputation and affect the high stock price. This research aimed to find out the effect of liquidity, sales growth, and company size variable to profitability variable in annual report listed on the Indonesia Stock Exchange year 2017–2019. The population are all food and beverage manufacturing companies listed on the Indonesia Stock Exchange, and obtained samples of amount 14 companies. The type of this research is a quantitative study. The data analysis used several analyzes, namely multiple linear analysis, the coefficient of determination test, the classical assumption test, R2 test, the F test, and the t test. Based on the results of this research, that partially liquidity has significant positive effect on profitability. Sales growth has no significant positive effect on profitability. Company size variable has no significant positive effect on profitability. The results of F test show that liquidity, sales growth, and company size have no effect on profitability.